2011
DOI: 10.1039/c1jm11351h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photocatalytic activity of iodine-doped ZnO nanoflowers

Abstract: The paper reports on the preparation and photocatalytic activity of thin films of iodine-doped ZnO nanoflowers deposited on glass substrate using a simple growth process based on hydrothermal synthesis. Addition of iodic acid (5-20 vol%) in the reaction mixture allows the introduction of iodine ions in the form of I or IO3 in the ZnO lattice, as suggested by X-ray photoelectron spectroscopy. Doping ZnO nanostructured films with iodine did not impact their morphology, while it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 27 publications
5
50
0
Order By: Relevance
“…5, which is at variance with experiment44. This is due to the low dopability of I, which result in precipitates at high doping concentrations44. This is in fact in line with the current calculations because E for of I is bigger than for F by ~2 eV (see Supplementary Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5, which is at variance with experiment44. This is due to the low dopability of I, which result in precipitates at high doping concentrations44. This is in fact in line with the current calculations because E for of I is bigger than for F by ~2 eV (see Supplementary Fig.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, I is expected to be an electron donor from Fig. 5, which is at variance with experiment44. This is due to the low dopability of I, which result in precipitates at high doping concentrations44.…”
Section: Discussionmentioning
confidence: 74%
“…To disclose the effects of the acetate and zinc ions in the reaction, we replaced Zn(NO 3 ) 2 with zinc acetate (Zn(OAc) 2 ) and ensured that the other conditions were the same, or increased the amount of Cu(OAc) 2 and kept the Zn(NO 3 ) 2 content constant.…”
Section: Preparation Of Zn-doped Cu 2 O Under Hydrothermalmentioning
confidence: 99%
“…17,18 Recently, Boukherroub et al synthesized iodine-doped ZnO (ZnO:I) nanoflower photocatalytic films for dye degradation, and they found that such hybrid films possessed significantly enhanced visible-light photocatalytic performance in comparison to that of undoped ZnO. 19 Accordingly, a deep exploitation of a versatile ZnO:I based photocatalyst via control of structural and compositional characteristics has great significance for more effective pollutant degradation and practical application, which has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%